Implementasi Metode Natural Approach dalam Pengajaran Bahasa Inggris di Sekolah Dasar - Achmad, Ali (Institut Agama Islam Negeri Palopo, 2013)
There are still many critics criticizing output of English teaching and learning process in the classroom in all level of education. These critical opinions bring the teachers about trying a new approach of teaching to find an appropriate way to help the students mastering English. This study aims to present the implementation of Natural Approach in the process of teaching and learning in the classroom, especially in the third class of Samawi Islamic Elementary School. Multiple intelligence theory, as a new unique way to analyze the studentsâ intelligent and help them to maximize their ability, is also adopted in this study. This adoption result from a variety of ability that the students in the classroom have.